“Pelos frutos os conhecereis”: um estudo sobre a religião da mente sadia e a religião da mente doentia de acordo com a experiência de membros de igrejas cristãs do grande Recife a partir do pensamento de William James. - Araújo, Maria Betânia Melo de (2021)
Based on the assumption that religion represents an integral element of human experience, this research has, as its object of study, the healthy and sick aspects of religious experience. The general objective is to analyze the healthy and unhealthy aspects of religion in followers of Christian churches in Greater Recife, based on and referenced in the notions of healthy mind religion and unhealthy mind religion, presented by American philosopher and psychologist William James, in his work entitled The Varieties of Religious Experience: A Study in Human Nature. The specific objectives were: To describe the figure of William James, focusing on the historical roots of the philosophical movements that influenced the construction of his system of thought, his personal journey, his work, the main concepts he elaborated and the influence exerted on the generation of scientists of the 19th and 20th centuries; analyze the notion of religious experience in William James in the general context of his work; understand the healthy and sick aspects of religion according to William James' thought; analyze, from the research carried out with the followers of Christian churches in Greater Recife, the characteristics of a healthy religion and an unhealthy religion in contemporary times. The guiding question posed in this research is: how can William James' thought on healthy religion and unhealthy religion be verified in followers of Christian churches in Greater Recife? The methodological procedures used have, as theoretical basis, the thought of James. The first stage of the research consisted in reading his work entitled The Varieties of Religious Experience: A Study in Human Nature and of authors who have taken positions on this work. The second stage of the research was characterized by the application of two of the qualitative approach's own resources: The Anonymous Public Opinion Questionnaire (APOQ) and the Interview. The people interviewed were selected from among the respondents to the questionnaire who were willing to do so. The data analysis was based on the Content Analysis. Therefore, it is a qualitative survey, which includes a bibliographic survey and a field survey. The research led us to conclude that one cannot propose a dichotomy, but the recognition of the existence and staggering of the healthy and sick aspects of religion. It is from this posture that we can analyze religious behavior and its expressions in daily life.